Respostas
respondido por:
10
3x + 10 = 4x + 8
3x - 4x + 10 - 8 = 0
-x + 2 = 0
-x = -2 (-1)
x = 2
2 é uma raiz da equação!
3x - 4x + 10 - 8 = 0
-x + 2 = 0
-x = -2 (-1)
x = 2
2 é uma raiz da equação!
ingridsl10:
muito obrigado mesmo!
respondido por:
15
3x + 10 = 4x + 8
3x - 4x + 10 - 8 = 0
3x - 4x = 0 + 8 - 10
- 1x = - 2
x = - 2 / - 1
x = 2
RESP = 2 é a raiz da equação.
Espero ter ajudado e bons estudos!
3x - 4x + 10 - 8 = 0
3x - 4x = 0 + 8 - 10
- 1x = - 2
x = - 2 / - 1
x = 2
RESP = 2 é a raiz da equação.
Espero ter ajudado e bons estudos!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás